2012
DOI: 10.1590/s0034-71672012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção de doenças sexualmente transmissíveis na visão de idosos de uma Estratégia da Saúde da Família

Abstract: The aim of this study was to assess the knowledge of elderly people on preventive actions to sexually transmitted diseases (STDs) in the context of the Family Health Strategy (FHS). This is a cross-sectional study, involving 94 elderly, aged ≥ 60 years, attached to the ESF in Serra Gaucha (a region at Rio Grande do Sul, Brazil). The results indicate parity in the sample for sexual activity and prevalence of sexual activity with the same partner. Older people have knowledge of how to prevent STDs, mostly by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
(2 reference statements)
1
9
0
6
Order By: Relevance
“…this result was corroborated by a study [14] conducted with 94 elderly, where only 24.5% reported having received counseling about sexually transmitted diseases during nursing visits, showing that users require assistance that emphasizes sexuality in aging.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…this result was corroborated by a study [14] conducted with 94 elderly, where only 24.5% reported having received counseling about sexually transmitted diseases during nursing visits, showing that users require assistance that emphasizes sexuality in aging.…”
Section: Discussionmentioning
confidence: 58%
“…With regard to condom use, most elderly people found this to be the best prevention for the disease. A study [14] that aimed to evaluate the knowledge of seniors on preventive actions for StIs in primary care showed that 90.1% of respondents believed that the use of condoms is the safest method to prevent contamination by the virus. However, the same study found that, when asked about sexual behavior, older people reported not having used a condom in some sex in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…É certo que o aumento do número de idosos, as oportunidades de interação social e a melhoria da qualidade de vida possibilitaram mudanças de comportamento relacionadas à sexualidade. Infelizmente, ainda é excludente a maneira como vem sendo abordada a sexualidade das pessoas idosas, distantes de projetos e programas de educação e prevenção de IST (Cezar, Aires, & Paz, 2012). Esse descompasso entre as oportunidades oferecidas para manter a sexualidade nos idosos e a pouca oferta de informações a respeito das IST contribuem para uma lacuna de conhecimentos e geração de equívocos na interpretação de ocorrências de contaminação entre idosos por HIV/Aids.…”
Section: Negociação De Uso Do Preservativo Entre Os Pares Idosos: Entunclassified
“…Society deprives the elderly of rethinking their own sexuality, libido, pleasure and sexual practice, causing difficulties of adaptation in this stage of life. With the passage of time, sexually transmitted diseases in the third age began to assume worrying rates (CEZAR; AIRES; PAZ, 2012). According to the same authors, these data are related to the failures that occur in the actions of education, promotion and prevention in health related to sexuality in the elderly.…”
Section: Introductionmentioning
confidence: 99%